Between path dependencies and renewable energy potentials: A case study of the Egyptian power system. (May 2022) - Dallmann, Christoph; Schmidt, Matthew; Möst, Dominik
Abstract: Egypt's power system is facing major changes. Rising demand, scarcity of fossil resources and the falling capital costs of solar and wind energy technologies pose the potential to fundamentally remake the national power fleet. Against this backdrop, the paper at hand investigates potential pathways of the domestic power system with a particular focus on regional deployment and associated impacts on the transmission network. To this end, the open-source modelling framework OSeMOSYS was adapted and deployed. The analysis evaluates renewable energy potentials for 320 sites across Egypt in eight different sub-regions. The study concludes that wind and PV installations prove to be cost-competitive and capable of shouldering a large share of projected demand growth, while their regional deployment should take required grid investments into consideration. The results also indicate that a restrained expansion of renewable energy technologies targeted by the government proves to be more costly than a more aggressive deployment pathway. Highlights: Cost-optimal future development of the Egyptian power plant fleet. Inclusion of renewable potentials for 320 sites across Egypt. Regional implications for the domestic transmission network.